Automated testing of Simulink models for real-time test environments - Balakrishnan Asokan, Dineshkumar (My University, 2023)
During the development phase of next-generation electric vehicles, which combine embedded systems and hardware with hundreds of thousands of lines of code, continuous testing and fast feedback are essential. To assure the highest possible quality, we utilize Hardware-In-the-Loop (HIL) simulators which enable software testing on the target electronic control unit (ECU) before there even is a car.This testing requires high-quality and reliable HIL models that simulate the ECU interfaces, as in the car, and live up to the requirements for SW testing. An ever-growing amount of different vehicle and drivetrain variants also impacts our real-time simulation models, so they become more complex and require better and faster testing This thesis focuses to automate the design and verification of simulation environments modelled in Simulink, and to create an automated process that generates tests and verifies our Simulink models. This will be an enabler to increase the pace of our deliveries and improve the quality of our real-time testing environments, crucial for electric vehicle software development.
Keywords: Hardware-In-the-Loop